PENGARUH VARIASI TARGET GAME TERHADAP PENING-KATANKETEPATAN PUKULAN SMASH BULU TANGKIS - Yusup Yusup; Fitriana Puspa Hidasari; Mimi Haetami (Universitas Tanjungpura, 2020)
AbstractThe research is backed by the precision of the badminton smash Punch which is relatively less accurate due to the lack of exercise variations and lack of special exercises to improve the precision of smash punch. The purpose of this research is to know the influence of game targets to increase the precision of badminton smash Punch. This research uses the form of Pre-Expermental Design that is one group Pretest-posttest design with a treatment of 12 times the meeting. This design has pre-test and posttest to compare the condition before and after being given treatment, The subject in this study was all the participants of the badminton extracurricular in the state Junior high School 03 Sungari Raya amounted to 25 people. The test in this study used test-T SPSS 25. Based on the research results can be concluded: There is a variation in game targets to increase the precision of badminton smash punch. With the value of Sig 0.000 < 0.05, then the target games variation method can be used as one of the effective exercise programs to improve the precision of the smash punch. Keywords: Variation Of Game Targets, Accuracy, Badminton